2009
DOI: 10.3899/jrheum.081321
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Necrosis Factor-α-blocking Agent Infliximab Inhibits Interleukin 1ß (IL-1ß) and IL-6 Gene Expression in Human Osteoblastic Cells

Abstract: The finding of downregulation of inflammatory cytokines was interesting, particularly IL-6, which plays a crucial role in arthritis-related bone loss due to its involvement in osteoclast recruitment and activation. These results may represent a biological explanation and a link for the clinical observation of the beneficial effects of anti-TNF-alpha agents on the progression of rheumatic diseases at the bone level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…Additionally, osteoblast-like cells, exposed to sera of RA patients treated with Infliximab, a TNF-α blocking agent, show a reduced synthesis of IL-6, a cytokine directly involved in arthritis-related bone loss (Musacchio et al 2009) Other factors that are present in the arthritic bone microenvironment and that seem to be involved in impaired bone formation include hypoxia and reduced pH. In vitro studies have demonstrated that these factors are able to down-regulate alkaline phosphatase synthesis in osteoblasts and to prevent mineralization (Utting et al 2006;BrandaoBurch et al 2005).…”
Section: Osteoblasts and Rheumatoid Arthritismentioning
confidence: 99%
“…Additionally, osteoblast-like cells, exposed to sera of RA patients treated with Infliximab, a TNF-α blocking agent, show a reduced synthesis of IL-6, a cytokine directly involved in arthritis-related bone loss (Musacchio et al 2009) Other factors that are present in the arthritic bone microenvironment and that seem to be involved in impaired bone formation include hypoxia and reduced pH. In vitro studies have demonstrated that these factors are able to down-regulate alkaline phosphatase synthesis in osteoblasts and to prevent mineralization (Utting et al 2006;BrandaoBurch et al 2005).…”
Section: Osteoblasts and Rheumatoid Arthritismentioning
confidence: 99%
“…TNF-a is a pleotropic cytokine that has many functions from cell migration to tissue destruction (Peschon et al 1998, Dinarello 2000, Wajant et al 2003, Kindle et al 2006. TNF-a up-regulates the production IL-1b and IL-6 (Okada et al 1997, Dinarello 2000, Wajant et al 2003, Kwan Tat et al 2004, Garlet et al 2007, Musacchio et al 2009). TNF-a is also correlated with extracellular matrix degradation and bone resorption through actions promoting secretion of MMPs and RANKL (Graves & Cochran 2003, Garlet et al 2004) and coupled bone formation (Behl et al 2008).…”
Section: Innate Immunity -The Inflammatory Responsementioning
confidence: 99%
“…This result show strong correlations with those earlier findings where the blockade of TNF-α by Remicade significantly reduced the relative gene expression of acute-phase proteins such as IL-1β and IL-6 [86]. Soluble TNF-α blockade also significantly down regulated CCL1 at relative gene expression ( Figure 16C) and secreted protein level ( Figure 16D) after prolonged PGN stimulation.…”
Section: The Blockade Of Soluble Tnf-α Significantly Reduces the Relasupporting
confidence: 81%